Pengaruh Jarak Tanam dan Dosis Poc Prolinak terhadap Pertumbuhan dan Hasil Padi (Oryza sativa L.) Varietas Inpari IR Nutri Zinc - Siti Zainab; Agung W. Wardana; Baharuddin; Zainal Arifin (Fakultas Pertanian - UMJ, 2025)
Rice (Oryza sativa L.) plays a vital role in ensuring food security, particularly in Indonesia, where it serves as the main dietary staple. This research aimed to evaluate how different planting distances and varying doses of liquid organic fertilizer influence the growth and productivity of the Inpari IR Nutri Zinc rice variety. It also explored the possible interaction between these two factors. The study was carried out from May to August 2022 in Kapu Hamlet, Sama Guna Village, Tanjung District, North Lombok. A Randomized Block Design (RBD) was employed, involving two variables: planting distance (20x20 cm, 20x25 cm, and 25x25 cm) and fertilizer dosage (10 ml/l, 20 ml/l, and 30 ml/l). Results revealed that planting distance had a significant impact on several growth indicators such as leaf count, number of tillers, panicle length, and grain weight per clump. The 25x25 cm spacing (J3) consistently yielded the most favorable outcomes across all metrics. Conversely, the application of liquid organic fertilizer at the tested doses had no notable effect on growth or yield. Additionally, no meaningful interaction was observed between planting distance and fertilizer dosage. Therefore, using the 25x25 cm spacing is recommended to optimize yield in Inpari IR Nutri Zinc rice cultivation